Strategi Pemasaran Bank Syariah DalamMeningkatkan Minat Generasi Milenial di Era Digital - Desi Susanti; Haniah Lubis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The development of Islamic banking in the digital era provides opportunities and challenges for its existence. So the Islamic bank must be able to use the existing opportunities as well as possible, namely by improving marketing strategies in the digital era by embracing the millennial generation. The purpose of this study was to determine the marketing strategy of Islamic banks in increasing the interest of the millennial generation in the digital era and also to find out the inhibiting factors in the marketing strategy carried out. the collection technique is through documentation. The analysis is descriptive qualitative. The results show that the marketing strategy of Islamic banks in increasing the interest of the millennial generation in the digital era can be carried out with a marketing mix strategy, namely: creating a condition called bank less (banks without offices), product innovations that can attract millennials namely marriage savings, and qurban savings (one people one goat), digital banks are able to save costs because they are easy, simple, and cheap, promotions by creating creative content competitions, promotions involving influencers/ustadz/artists, and promotions involving the active role of generations millennial. The inhibiting factors are: lack of application socialization by Islamic banks, untouched internet networks in remote areas, features that are still lacking in supporting marketing. Keywords: strategy, marketing, Islamic banking, millennials.